2013
DOI: 10.1038/jcbfm.2013.76
|View full text |Cite
|
Sign up to set email alerts
|

The APOE ε4/ε4 Genotype Potentiates Vascular Fibrin(Ogen) Deposition in Amyloid-Laden Vessels in the Brains of Alzheimer's Disease Patients

Abstract: Evidence indicates a critical role for cerebrovascular dysfunction in Alzheimer's disease (AD) pathophysiology. We have shown that fibrin(ogen), the principal blood-clotting protein, is deposited in the AD neurovasculature and interacts with beta-amyloid (Aβ), resulting in increased formation of blood clots. As apolipoprotein E (ApoE), a lipid-transporting protein with three human isoforms (E2, E3, and E4), also binds to Aβ, we hypothesized that ApoE and fibrin(ogen) may have a combined effect on the vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
135
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(148 citation statements)
references
References 38 publications
9
135
0
Order By: Relevance
“…Increases in CypA and MMP-9 CSF levels were recently reported to correlate with BBB breakdown in human APOE4 carriers, but not age-matched APOE2 or APOE3 carriers that have an intact BBB 49 . Additionally, post-mortem analysis in APOE4 -positive AD patients compared to non-carriers revealed increased CypA and MMP-9 protein levels in hippocampal and cortical pericytes as well as pericyte degeneration 50,151 .…”
Section: Pericyte-astrocyte Signal Transductionmentioning
confidence: 94%
“…Increases in CypA and MMP-9 CSF levels were recently reported to correlate with BBB breakdown in human APOE4 carriers, but not age-matched APOE2 or APOE3 carriers that have an intact BBB 49 . Additionally, post-mortem analysis in APOE4 -positive AD patients compared to non-carriers revealed increased CypA and MMP-9 protein levels in hippocampal and cortical pericytes as well as pericyte degeneration 50,151 .…”
Section: Pericyte-astrocyte Signal Transductionmentioning
confidence: 94%
“…Several studies of post-mortem brain tissue from patients with AD have found (using various analysis methods: immunohistochemistry, immunoblotting and Prussian blue staining) capillary leakages of blood-derived proteins in the prefrontal and entorhinal cortex and hippocampus, including accumulations of fibrinogen, thrombin, albumin, IgG, and iron-containing proteins such as haemosiderin 146,147,152157 . These blood-derived proteins are often found co-localized with deposits of AD-associated Aβ 147,153,155 .…”
Section: Postmortem Evidence Of Bbb Disruptionmentioning
confidence: 99%
“…These blood-derived proteins are often found co-localized with deposits of AD-associated Aβ 147,153,155 . Evidence of BBB breakdown is most pronounced in individuals carrying the APOE*ε4 allele, the major genetic risk factor for AD.…”
Section: Postmortem Evidence Of Bbb Disruptionmentioning
confidence: 99%
“…In fact, multiple studies demonstrated loss of cerebrovascular integrity and BBB damage, for example, on aging and in Alzheimer's disease, 18,20,21 that is accelerated by the apolipoprotein E4 (APOE4) genotype. 18,[21][22][23][24] Mechanistic studies using murine transgenic models showed that APOE4 increases BBB susceptibility to injury 25 and leads to BBB breakdown and microvascular reductions in humanized transgenic APOE4-knock-in mice compared with APOE3-knock-in mice.…”
mentioning
confidence: 99%
“…18,[21][22][23][24] Mechanistic studies using murine transgenic models showed that APOE4 increases BBB susceptibility to injury 25 and leads to BBB breakdown and microvascular reductions in humanized transgenic APOE4-knock-in mice compared with APOE3-knock-in mice. 26,27 The present study has been designed to test these hypotheses in patients having acute ischemic stroke in the middle cerebral artery (MCA) territory.…”
mentioning
confidence: 99%